Mengkaji Pengembangan E-Modul sebagai Media Pembelajaran: Sebuah Tinjauan Literatur - Kadek Dwi Wahyuni; Ketut Agustini; I Wayan Sudiartha (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Developing learning media in the digital age is an effort to optimize the learning process, making it more interactive, effective, and engaging. E-modules are a prime example of frequently developed learning media. This research aims to examine the e-module development process as both a learning and training tool. This study employs a systematic literature review method. The research questions address the development models, applications used, and success criteria for e-module creation. A total of 20 scholarly articles were reviewed using the PRISMA approach. The data analysis revealed that the ADDIE model is the predominant development model for e-module creation. Canva and Microsoft Office are the applications most frequently used to develop e-modules. Furthermore, the most common success criteria applied involve measuring the media's validity, practicality, and effectiveness. The findings from this literature review are ultimately expected to serve as valuable considerations and input for institutions and learning media developers in their ongoing efforts to develop e-modules as effective learning tools.